Endocrine Actions of Osteocalcin - Aurora Patti; Luigi Gennari; Daniela Merlotti; Francesco Dotta; Ranuccio Nuti (International Journal of Endocrinology)
Osteocalcin is the most abundant noncollagenous protein of bone matrix. Once transcribed, this protein undergoes posttranslational modifications within osteoblastic cells before its secretion, including the carboxylation of three glutamic residues in glutamic acid, which is essential for hydroxyapatite binding and deposition in the extracellular matrix of bone. Recent provocative data from experimental observations in mice showed that the circulating undercarboxylated fraction of osteocalcin increases insulin secretion and sensitivity, lowers blood glucose, and decreases visceral fat in both genders, while it enhances testosterone production by the testes in males. Moreover, both total and undercarboxylated osteocalcins increase following physical activity with potential positive effects on glucose tolerance. Despite that these evidences have been only in part confirmed in humans, further prospective investigations are needed to definitively establish the endocrine role of osteocalcin both in the general population and cohorts of patients with diabetes or other metabolic disorders.